The Impact of Macroeconomic Conditions on Long-Term Care: Evidence on Prices - Johannes Geyer; Peter Haan; Mia Teschner (Institute of Labor Economics (IZA), 2024)
The price for institutional long-term care is a central determinant of the demand for formal and informal long-term care. In this paper, we show how macroeconomic conditions affect these prices. The analysis is based on administrative data that contains rich information on the universe of nursing homes and ambulatory care services and about all recipients of long-term care benefits in Germany. For identification, we exploit variation in macroeconomic conditions measured by the unemployment rate across districts and over time, applying a panel data approach with facility and time fixed effects. Our empirical results show that a higher unemployment rate increases prices for permanent long-term care as well as for prices of accommodation and meals in nursing homes. We provide empirical evidence for the mechanism of these price effects. While we find that employment, working hours, and quality of care in nursing homes are not significantly affected by macroeconomic conditions, our results show that a higher unemployment rate increases the price of nursing homes through a change in the composition of patients: it induces a shift from care recipients with a low degree of impairment to patients with high demands for labor-intensive care. We also document a substitution of low-impairment care from nursing homes toward ambulatory and informal home care.
Keywords: E32; I11; J20; 330; long-term care; nursing home prices; unemployment rate; macroeconomic conditions; informal care